The Influence of Impulsive Attitudes in Developing Careers for Teenagers (Review of Maudhu'i's Interpretation) - Rifqon Hadi Attohiri; M Mukhid Mashuri; Miftara Ainul Mufid (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2025)
This study aims to explore impulsive attitudes in careers among adolescents using a library research approach. Impulsive or hasty attitudes are human tendencies that are often highlighted in the Qur'an as an innate character that needs to be controlled. In QS. Al-Isra' verse 11, Allah mentions that humans tend to be hasty in acting, even in things that are detrimental to themselves. This study aims to examine the impact of impulsive attitudes from the perspective of the Qur'an on adolescent career development. The results of the study indicate that uncontrolled impulsive attitudes can cause adolescents to make career decisions emotionally, inconsistently, and less considering the long term. The Qur'an directs humans to be patient, think carefully (tafakkur), and not follow their lusts in making decisions. Therefore, Qur'anic values can be a preventive solution in forming the character of adolescents who are wiser and more visionary in designing their future careers. In an era of fast-paced information and full of external influences, adolescents are often faced with complex career choices, which can encourage irrational decision-making. Therefore, this study will explore various literature that discusses the influence of impulsive attitudes on career choices in adolescents and solutions to avoid them in the Qur'an, such as psychological, social, and cultural development.